Government Policy and Performance of Small and Medium Business Management - Eniola, Anthony A.; Harry, Entebang (HRMARS, 2015)
It is recorded that 99 per cent of the business bodies in Nigeria are MSMEs which has been an instrumental component in GDP and hub for work opportunities. Even so the identification of the important roles SMEs play in Nigeria, their evolution is mostly bounded by a number of elements, such as the existence of laws, ordinances, and rules that frustrate the growth of the sector. The study reviews the relationship between government policies and small and medium enterprises (SMEs) performance in Nigeria. The study offered some relevant recommendations to policy makers, entrepreneurs, and SME managers to ensure the appropriate scheme to improve the SME sector in Nigeria.